Myocardial contractile reserve predicts left ventricular reverse remodeling and cardiac events in dilated cardiomyopathy. Issue 4 (October 2017) - Morimoto, Ryota; Okumura, Takahiro; Hirashiki, Akihiro; Ishii, Hideki; Ichii, Takeo; Aoki, Soichiro; Furusawa, Kenji; Hiraiwa, Hiroaki; Kondo, Toru; Watanabe, Naoki; Kano, Naoaki; Fukaya, Kenji; et al.
Abstract: Background: Catecholamine sensitivity estimated using a dobutamine stress test (DST) is recognized as a measure of the beta-adrenergic myocardial contractile reserve, which is involved with left ventricular reverse remodeling (LV-RR). We investigated whether the prognostic ability of the DST for LV-RR could predict cardiac events. Methods: There was a total of 192 enrolled patients with dilated cardiomyopathy (DCM). DCM was defined as a LV ejection fraction (LV-EF) ≤45% and LV end-diastolic dimension (LVDd) ≥55 mm. One hundred patients were subjected to micromanometer-based measurement of the maximal first derivative of LV pressure (LVdP/dtmax ), an index of LV contractility, at baseline and following the infusion of dobutamine (10 μg/kg/min) via a pigtail catheter. Percentage changes in LVdP/dtmax from the baseline to peak values under dobutamine stress (ΔLVdP/dtmax ) were also calculated. After excluding 17 patients who received cardiac resynchronization therapy within 3 months of undergoing DST ( n = 15) and who did not receive follow-up echocardiography ( n = 2), 83 patients were enrolled (52.5 ± 12.3 years). Results: During the follow-up period (4.7 ± 2.6 years), LV-RR was recognized in 49 of 83 patients (59.0%). A multivariate logistic regression analysis revealed that ΔLVdP/dtmax (hazard ratio: 1.024, p = 0.007) and the symptom duration (hazard ratio: 0.977, p = 0.003) were independent predictors of LV-RR. A receiver operating characteristic curve analysis revealed a ΔLVdP/dtmax cut-off value of 75.1% for LV-RR and a significantly lower cardiac event rate in the ΔLVdP/dtmax ≥ 75.1% group ( p = 0.045). Conclusions: ΔLVdP/dtmax estimated using DST was a useful predictor of LV-RR and cardiac events in patients with DCM.